Teacher... What is your story? - Martínez Sánchez, Helena (Rastros Rostros, 2002)
This is the appropriate question for teachers who interact daily with the handful of children who come to school because they were sent home to study. The children want to continue at school with the experiences that are their daily routine at home: storytelling, painting, playing, writing, erasing, rewriting, reading happily, jumping, running. Far from their concerns and interests are homework, work discipline, compliance with a schedule, without ignoring that these are also indispensable situations for their personal growth, so it is difficult to think of them disappearing from school. It is up to the teacher to invent his or her own story, according to the previous interests of boys and girls, where it is possible for them to experience the moments of their school education with pleasure and accept school events as something natural and unprepared without feeling them as a torturous imposition.